Immunotherapy in Autoimmune and Neuroinflammation-Related Epilepsies - Arya, Kapil; Willis, Erin; Samanta, Debopam (Journal of Pediatric Epilepsy, 2018)
There is increasing recognition of the role played by neuroinflammation both as a factor in the development of epilepsy as well as a consequence of seizures. Autoimmune encephalitis and epilepsies have emerged as an important etiology of drug-refractory epilepsies. The recognition of these entities is vital for immunomodulation and is the cornerstone in its management. Immunotherapy treatment regimens in these conditions continue to be refined, and there is an increasing knowledge in their use. This article attempts to review the experience with the use of different immunotherapies in specific autoimmune and neuroinflammation-related encephalitis and epilepsies including their mechanisms of action and potential side effects.
Keywords: neuroinflammation; epilepsy; therapy